Fabrication and characterization of polylactic acid/natural fiber extruded composites. Issue 4 (21st February 2023) - Alothman, Othman Y.; Awad, Sameer; Siakeng, Ramengmawii; Khalaf, Eman M.; Fouad, Hassan; Abd El‐salam, Nasser M.; Ahmed, Faraz; Jawaid, M.
Abstract: In this work, the fabricated polylactic acid (PLA) and hybrid natural fiber (NF) biocomposites via a melt extrusion method were investigated. NFs from locally grown plants were utilized as fillers. Polyethene glycol (PEG) was used as the plasticizer to improve the processability of the PLA. The effect of PLA/NF biocomposite processing was assessed by mechanical characterization (tensile, modulus, strain at break, and impact tests), and thermal properties (thermogravimetric analysis and differential scanning calorimetry [DSC] analysis). The dynamic mechanical analysis (DMA), and thermo‐mechanical analysis (TMA) of the samples were also analyzed. The mechanical properties of PLA/NF biocomposites improved as compared with that of PLA. The DMA findings show that the storage modulus and loss modulus exhibited a slight reduction for PLA/NF biocomposites compared with the PLA sample. In opposite, the glass transition temperature ( T g ) from DSC thermogram results showed no obvious changes in values compared with the PLA sample. Furthermore, the findings of TMA showed a significant decrease in coefficient of thermal expansion values of PLA/NF biocomposites compared with those of PLA samples. The overall findings from this work indicated that PLA/NF biocomposites have the potential to make novel biocomposites and suitable for further application especially in biomedical applications due to its good stiffness, tensile strength, and dimensional stability. Abstract : FTIR spectra of natural fibre/PLA biocomposites.